Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry for Differentiation of the Dimorphic Fungal Species Paracoccidioides brasiliensis and Paracoccidioides lutzii - Almeida, Joao Nobrega de; Del Negro, Gilda M. B.; Grenfell, Rafaella C.; Vidal, Monica S. M.; Thomaz, Danilo Y.; De Figueiredo, Dulce S. Y.; Bagagli, Eduardo [UNESP]; Juliano, Luiz; Benard, Gil (Amer Soc Microbiology, 2015)
Isolates of Paracoccidioides brasiliensis and Paracoccidioides lutzii, previously characterized by molecular techniques, were identified for the first time by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). All isolates were correctly identified, with log score values of >2.0. Thus, MALDI-TOF MS is a new tool for differentiating species of the genus Paracoccidioides.